The impact of the variation in vertical load and the presence of openings on the mechanical response of masonry walls - Khanfri Chaimae; Mouhat Ouadia; Elrhaffari Younes; El Mennaouy Fatima; Rougui Mohamed (E3S Web of Conferences, 2025)
This article aims to analyse the mechanical response of masonry walls under cyclic loading using the finite element method with Abaqus software. The proposed model has been validated using available numerical and experimental results. This work provides an in-depth study of the cracking modes of masonry walls based on different vertical loads and the presence of openings. By using numerical simulations, it identifies the types of cracks that develop, their propagation, and their interaction with the structure. A parametric study will then be conducted to assess the influence of variations in vertical load and the effect of openings on the behaviour of the walls. Load-displacement curves and failure modes are presented and analysed. The results show that these parameters have a significant impact on wall behaviour. Specifically, an increase in vertical load improves the wall's resistance, while openings create weakness zones that promote degradation and reduce strength. A thorough understanding of the behaviour of unreinforced masonry structures is essential for making informed decisions regarding restoration methods.